The relationship between servant leadership, work engagement and perceived organization support towards organisational citizenship behaviour at Langkawi tourism @ KK Langkawi - Siti Aishah, Edros (2016)
The purpose of this study is to identify the correlation between servant leadership, work engagement and perceived organizational support (POS) towards organizational citizenship behaviour (OCB) at Langkawi Tourism Academy@KKLangkawi. Census method was used in this study by using questionnaire for data collection. The population of this study are 70 respondent. Whole populations were the respondent for this study. The 70 questionnaires were distributed to the employee at Langkawi Tourism Academy@KKLangkawi, out of 70 questionnaire, 57 were returned and valid to be analyze. In its empirical analysis, the study used the SPSS version 20.0. The finding of this study reveals that Servant Leadership, Work Engagement and POS are positively significant with OCB. This study shows that the most dominate factor that affecting the OCB are POS with p-value are 0.048. POS are the most elements that contribute the successful OCB level in Langkawi Tourism Academy@KKLangkawi. Finally this study given an information to the management that servant leadership, work engagement and POS need be priority attention. Furthermore, result shows that POS are the most prioritizes for the management to be engaged.